La innovación en el turismo gastronómico, como alternativa de desarrollo sostenible en la parroquia Taquil - Pilco Paladines, Peter Andrés (2023)
Food tourism is an increasingly popular way to travel and experience new cultures through their food; That is why this paper focuses on innovation in gastronomic tourism, whose objective is to propose a strategic innovation plan to strengthen gastronomic tourism in the Taquil parish. In this sense, a type of participatory action research was used, with a non-experimental, cross-sectional, descriptive approach. For the diagnosis of gastronomic tourism in the parish, the MINTUR File was used and a semi-structured interview was applied to eight professionals and gastronomic experts from the city of Loja. The main results, allowed to know that the gastronomic offer of the Taquil parish, is made up mainly of three restaurants, the same ones that provide their food services permanently. A total of 16 products offered by the food service providers of this parish were established, highlighting the Sango de maíz, Cuy asado, Creole chicken broth and Fried trout. In addition, it was determined that entrepreneurs provide five services in total; Food, Camping, Cinema, Kaffecombi and Lodging. According to the perceptions of the gastronomy experts who participated in the investigation, it is concluded that the Taquil parish has a high potential for the development of gastronomic tourism; however, to improve it, it is recommended, among other alternatives, the introduction of new dishes on the menu. Finally, the proposal for gastronomic innovation includes the redesign of the traditional recipes of the main gastronomy of the parish, to go from traditional food to a new style of cooking, which would be signature cuisine and also market cuisine, as well The use of clay tableware that is made in the Cera community of this parish is proposed, in order to involve the population and contribute to sustainable development and gastronomic tourism in the Taquil parish.